ESTIMATION OF POTATO ACREAGE IN THE INDO-GANGETIC REGION USING IRS AWIFS DATA - Dua, V K; Panigrahy, Sushma; Mehta, R L; Lal, S. S.; Govindakrishnan, P M.; Singh, J P; Arora, R K; Kumar, Manoj; Kumar, Parveen; Rawat, Shashi; Bhatt, Nitin; Ahmad, Islam (Potato Journal, 2013)
IRS P6 AWiFS data were used for the potato acreage estimation in dominant potato growing areas in the Indo-Gangetic region of India. Results showed that data acquired during near peak vegetative period is optimum for classification of potato crop. This period varies significantly across the IndoGangetic plains. Around 90% classification accuracy was obtained for dominant potato growing districts of five states (Punjab, Haryana, UP, Bihar and West Bengal).